Identifikasi Hidrogen Peroksida (H2O2) Pada Bihun Yang Diperjualbelikan Di Kota Makassar - Rahmawati Rahmawati; Hasnah Hasnah; Waode Rustiah; Suci Alya Hamran (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2023)
Vermicelli is a type of noodle made from white rice flour that can be used as an alternative to rice, which contains carbohydrates. The nutritional value of vermicelli will decrease because producers often use various methods to achieve an attractive appearance. One common method is to add bleach to vermicelli, such as hydrogen peroxide (H2O2). Hydrogen peroxide is a food additive that is officially prohibited according to Regulation No. 33 of the Minister of Health of the Republic of Indonesia. The use of hydrogen peroxide (H2O2) is not justified because it is dangerous and can have a negative impact on the body when consumed, such as vomiting, diarrhea, headaches, and gastrointestinal bleeding, which leads to a burning sensation in the stomach. This study aims to identify hydrogen peroxide (H2O2) in vermicelli that is traded in traditional markets in Makassar City. The type of research used is laboratory observation with a qualitative approach. The sampling technique was carried out by purposive sampling using the color test reaction method. The results showed that out of 10 vermicelli samples, 9 were negative and 1 was positive for hydrogen peroxide, which was marked by a change in color from white to purple. Thus, it can be concluded that 1 out of 10 samples of vermicelli that are traded in traditional markets in Makassar city contain hydrogen peroxide (H2O2).